2002
DOI: 10.1136/adc.87.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Airway resistance measured by the interrupter technique: normative data for 2-10 year olds of three ethnicities

Abstract: Background and Aims: The measurement of airway resistance using the interrupter technique (R int ) is feasible in preschool children and other subjects unable to undertake spirometry. This makes it potentially useful for the measurement of lung function in these groups. Commercial devices use different algorithms to measure pressure and flow from which R int is derived. This study provides normative values for British children using devices from a single manufacturer. Methods: R int was measured in 236 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 23 publications
4
48
2
2
Order By: Relevance
“…17 Interestingly, Rint values expressed as absolute and z-scores were significantly higher in preterm children in this study (1.16 and 1.00 kPa l À1 s) compared to healthy controls in a recent study (0.70 and 0.0 kPa l À1 s). 26 Thus, Rint is also able to discriminate between prematurely born children without CLD and healthy controls as shown previously.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…17 Interestingly, Rint values expressed as absolute and z-scores were significantly higher in preterm children in this study (1.16 and 1.00 kPa l À1 s) compared to healthy controls in a recent study (0.70 and 0.0 kPa l À1 s). 26 Thus, Rint is also able to discriminate between prematurely born children without CLD and healthy controls as shown previously.…”
Section: Discussioncontrasting
confidence: 43%
“…The baseline differences found between the study groups were in accordance with a previous study. 26 Although Rint is related to both age and height 17 its correlation with birthweight and gestation is not known. It is plausible that the baseline difference in neonatal gestation and birth weight in CLD group may be responsible for the increased Rint in this study, though this baseline difference did not influence Rint in the study by Vrijlandt et al 26 Furthermore; anthropometric data including weight, height and corrected age were comparable between the groups at the time of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The user-friendliness of the technique and the portability of the equipment, as well as the possibility of a correlation between Rint and spirometric values, have increased the interest in the method and its use in children and adolescents with pulmonary disease. (3,(7)(8)(9)(10)(11)(12)(13)(14) Many patients with CF use bronchodilators to relieve their symptoms or prior to physical therapy, and the measurement of bronchodilator response is an important part of the follow-up of such patients. In studies involving asthma patients, the Rint technique was shown to be accurate in measuring such a response.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure is measured using two points by linear back-extrapolation. (5,14,15) Flow and pressure calibration of the MicroRint ® , accurate to within 1%, was carried out every 50 measurements, using a manometer and a 3-L syringe.…”
Section: Introductionmentioning
confidence: 99%